Non-classical Vitamin D Actions for Renal Protection - Dusso, Adriana S.; Bauerle, Kevin T.; Bernal-Mizrachi, Carlos (Frontiers in Medicine, 2021)
Chronic Kidney Disease (CKD), a disorder that affects 11% of the world's population, is characterized by an acceleration in skeletal, immune, renal, and cardiovascular aging that increases the risk of cardiovascular mortality by 10- to 20-fold, compared to that in individuals with normal renal function. For more than two decades, the progressive impairment in renal capacity to maintain normal circulating levels of the hormonal form of vitamin D (1,25-dihydroxyvitamin D or calcitriol) was considered the main contributor to the reduced survival of CKD patients. Accordingly, calcitriol administration was the treatment of choice to attenuate the progression of secondary hyperparathyroidism (SHPT) and its adverse impact on bone health and vascular calcification. The development of calcitriol analogs, designed to mitigate the resistance to calcitriol suppression of PTH associated with CKD progression, demonstrated survival benefits unrelated to the control of SHPT or skeletal health. The exhaustive search for the pathophysiology behind survival benefits associated with active vitamin D analogs has identified novel anti-inflammatory, anti-hypertensive, anti-aging actions of the vitamin D endocrine system. A major paradigm shift regarding the use of calcitriol or active vitamin D analogs to improve survival in CKD patients emerged upon demonstration of a high prevalence of vitamin D (not calcitriol) deficiency at all stages of CKD and, more significantly, that maintaining serum levels of the calcitriol precursor, 25(OH)vitamin D, above 23 ng/ml delayed CKD progression. The cause of vitamin D deficiency in CKD, however, is unclear since vitamin D bioactivation to 25(OH)D occurs mostly at the liver. Importantly, neither calcitriol nor its analogs can correct vitamin D deficiency. The goals of this chapter are to present our current understanding of the pathogenesis of vitamin D deficiency in CKD and of the causal link between defective vitamin D bioactivation to calcitriol and the onset of molecular pathways that promote CKD progression independently of the degree of SHPT. An understanding of these mechanisms will highlight the need for identification of novel sensitive biomarkers to assess the efficacy of interventions with vitamin D and/or calcitriol(analogs) to ameliorate CKD progression in a PTH-independent manner.